Fine structure of the "PcG body" in human U-2 OS cells established by correlative light-electron microscopy - Smigová, Jana; Juda, Pavel; Cmarko, Dušan; Raška, Ivan (Nucleus (Austin, Tex.), 2011)
Polycomb group (PcG) proteins of the Polycomb repressive complex 1 (PRC1) are found to be diffusely distributed in nuclei of cells from various species. However they can also be localized in intensely fluorescent foci, whether imaged using GFP fusions to proteins of PRC1 complex, or by conventional immunofluorescence microscopy. Such foci are termed PcG bodies, and are believed to be situated in the nuclear intechromatin compartment. However, an ultrastructural description of the PcG body has not been reported to date. To establish the ultrastructure of PcG bodies in human U-2 OS cells stably expressing recombinant polycomb BMI1-GFP protein, we used correlative light-electron microscopy (CLEM) implemented with high-pressure freezing, cryosubstitution and on-section labeling of BMI1 protein with immunogold. This approach allowed us to clearly identify fluorescent PcG bodies, not as distinct nuclear bodies, but as nuclear domains enriched in separated heterochromatin fascicles. Importantly, high-pressure freezing and cryosubstitution allowed for a high and clear-cut immunogold BMI1 labeling of heterochromatin structures throughout the nucleus. The density of immunogold labeled BMI1 in the heterochromatin fascicles corresponding to fluorescent "PcG bodies" did not differ from the density of labeling of heterochromatin fascicles outside of the "PcG bodies". Accordingly, an appearance of the fluorescent "PcG bodies" seems to reflect a local accumulation of the labeled heterochromatin structures in the investigated cells. The results of this study should allow expansion of the knowledge about the biological relevance of the "PcG bodies" in human cells.
Keywords: Microscopy, Electron; nádorové buněčné linie; Light; Heterochromatin; kryoprezervace; elektronová mikroskopie; Cryopreservation; represorové proteiny; imunohistochemie; high-pressure freezing; světlo; Polycomb group proteins; tlak; Pressure; Cell Line, Tumor; heterochromatin; Polycomb-Group Proteins; Repressor Proteins; PcG body; Immunohistochemistry; BMI1 protein; Humans; polycomb proteiny; correlative light-electron microscopy; immunogold labeling; lidé